The Effect of Albendazole on the Prevention of Secondary Hydatidosis - Erzurumlu, K; Hokelek, M; Gonlusen, L; Tas, K; Amanvermez, R (HGE Update Medical Publishing SA, 2000)
BACKGROUND/AIMS: Secondary hydatidosis and recurrence are serious complications in hydatid surgery. Although medical treatment and current surgical techniques are more effective in the prevention of cyst formation resulting from spillage of cystic liquid, secondary hydatidosis is still surgically important. Albendazole, a derivative of benzoimidazole, is the most commonly used drug in the medical treatment of echinococcosis. The effectiveness of pre-operative prolonged or single dose applications is supported by the literature. METHODOLOGY:, Twenty-two cases of hepatic hydatidosis are-evaluated and treated by surgery. Perioperative albendazole treatment was given in a dose of 12-15mg/kg/day in 4 divided doses. The treatment began 5-20 days before the surgery and continued 3-7 months in a cyclic monthly form, until latex agglutination tests were negative. In the postoperative period, hematological, ultrasonography and computed tomography scan evaluation was-carried out. The follow-up period for 21 patients was 6-31 months (mean: 20.52 months). RESULTS: There was no secondary hydatidosis, recurrence or mortality in this study. Early and late morbidity rates were 4.54% and 13.63% respectively. CONCLUSIONS: Our results support that perioperative albendazole treatment is effective in the prevention of secondary hydatidosis.
Keywords: Hydatid Disease; Albendazole; Perioperative Treatment